Anal swab as the potentially optimal specimen for SARS-CoV-2 detection to evaluate the hospital discharge of COVID-19 patients - Sun, Mei (Future Microbiol, 2020)
Since December 2019, an outbreak of SARS coronavirus 2 (SARS-CoV-2) began in Wuhan, and has rapidly spread worldwide. Previously, discharged patients with coronavirus disease 2019 (COVID-19) patients met the criteria of China’s pneumonia diagnosis and treatment program of novel coronavirus infection (trial version 7) for cure of viral infection. Nevertheless, positive detection of SARS-CoV-2 has been found again in several cured COVID-19 patients, leading to conflicts with current criteria. Here, we report clinically cured cases with positive results only in anal swabs, and investigate the clinical value of anal swabs for SARS-CoV-2 detection.